2019
DOI: 10.1155/2019/2580409
|View full text |Cite
|
Sign up to set email alerts
|

Danshenol A Alleviates Hypertension-Induced Cardiac Remodeling by Ameliorating Mitochondrial Dysfunction and Suppressing Reactive Oxygen Species Production

Abstract: Current therapeutic approaches have a limited effect on cardiac remodeling, which is characteristic of cardiac fibrosis and myocardial hypertrophy. In this study, we examined whether Danshenol A (DA), an active ingredient extracted from the traditional Chinese medicine Radix Salviae, can attenuate cardiac remodeling and clarified the underlying mechanisms. Using the spontaneously hypertensive rat (SHR) as a cardiac remodeling model, DA ameliorated blood pressure, cardiac injury, and myocardial collagen volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Under normal physiological conditions, 90% of the energy required by the heart is derived from mitochondrial OXPHOS, and normal mitochondrial function is a necessary prerequisite for the maintenance of the heart pumping function. Recently, increasing data have shown that mitochondrial dysfunction is involved in the occurrence of cardiac diseases, such as cardiac hypertrophy, myocardial fibrosis (Chen et al, 2019), diabetic cardiomyopathy (Gollmer et al, 2020), and heart failure (Kumar et al, 2019). Accumulating evidence has also suggested that targeting mitochondrial function may represent a promising potential therapeutic strategy for addressing heart failure (Brown et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under normal physiological conditions, 90% of the energy required by the heart is derived from mitochondrial OXPHOS, and normal mitochondrial function is a necessary prerequisite for the maintenance of the heart pumping function. Recently, increasing data have shown that mitochondrial dysfunction is involved in the occurrence of cardiac diseases, such as cardiac hypertrophy, myocardial fibrosis (Chen et al, 2019), diabetic cardiomyopathy (Gollmer et al, 2020), and heart failure (Kumar et al, 2019). Accumulating evidence has also suggested that targeting mitochondrial function may represent a promising potential therapeutic strategy for addressing heart failure (Brown et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[23] DA ameliorates myocardial fibrosis by inhibiting mitochondrial dysfunction and reducing reactive oxygen species production. [24] The biological effects exhibited by these compounds suggest that YTG may act as an antifibrotic agent through multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are the necessary energy supply organelles to maintain the normal morphology and function of cardiomyocytes. 22,23 The ATP assay showed that ISO inhibited the expression of ATP, while it could be alleviated by S-CPDs (Fig. 3a).…”
Section: Papermentioning
confidence: 99%